2021
DOI: 10.1055/s-0041-1735206
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Pacemaker-Induced Cardiomyopathy Incidence and Predictors in Patients with Right Ventricular Pacing: A Systematic Review

Abstract: This study aimed to figure out the incidence and predictors of pacemaker-induced cardiomyopathy (PICM) in patients with right ventricular (RV) pacing. We systematically searched in PubMed on March 18, 2020, for English language abstract and full-article journals, using the following criteria: pacemaker induced cardiomyopathy AND right ventricular AND pacemaker AND patients AND human NOT implantable cardioverter defibrillator NOT ICD NOT animal. Four studies were included in this review after filtering 35 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 17 publications
(77 reference statements)
0
15
1
Order By: Relevance
“…In comparison to patients with previously normal LV function, there was an overall trend towards improvement of LV function in patients with underlying cardiomyopathies following pacemaker implantation. Although this did not correlate with degree of RV pacing, the proportion of patients that had a significant fall in LV function following pacemaker implantation (17.2%) is higher than previously reported PICM rates of 5%–15% in those with baseline normal EF 1,2 . This likely reflects the often progressive nature of heart failure.…”
Section: Discussioncontrasting
confidence: 56%
“…In comparison to patients with previously normal LV function, there was an overall trend towards improvement of LV function in patients with underlying cardiomyopathies following pacemaker implantation. Although this did not correlate with degree of RV pacing, the proportion of patients that had a significant fall in LV function following pacemaker implantation (17.2%) is higher than previously reported PICM rates of 5%–15% in those with baseline normal EF 1,2 . This likely reflects the often progressive nature of heart failure.…”
Section: Discussioncontrasting
confidence: 56%
“…Each year, more than 700,000 new permanent pacemakers are implanted and more than 200,000 patients have permanent pacemakers replaced. 4 A prospective study by Carrión-Camacho and colleagues revealed that 1.25 million pacemakers are implanted every year worldwide. 9 RV apical pacing has been the only effective treatment of choice for symptomatic sinus node dysfunction and high-degree AV block.…”
Section: Epidemiologymentioning
confidence: 99%
“…Pacemaker-induced cardiomyopathy (PICM) is a new type of cardiomyopathy that has been recognized in recent years because of the increasing number of patients with permanent pacemakers and associated heart failure. According to Laksono and colleagues, studies have revealed that the incidence of PICM ranges from 10.7% to 13.7% 4. In addition, a recent study revealed that the incidence of PICM can develop in 5.9% to 39% of patients 3 to 4 years after pacemaker implantation 5.…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations